2016
DOI: 10.32360/acmar.v49i1.6167
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Marine Catches Off the State of Sergipe (1950-2010)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
0
4
0
10
Order By: Relevance
“…Mugil hospes Jordan & Culver, 1895 was also recorded in the province but was later identified as M. brevirostris (Ribeiro, 1915) (Menezes et al., 2015). The presence of M. incilis Hancock, 1,830 in this region remains uncertain: a review of mullet species of South America indicated that this species does not reach the Tropical Southwestern Atlantic (Menezes et al., 2015), while some authors continue to record the species in the area (e.g., Barletta & Dantas, 2016; Freire & Araújo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mugil hospes Jordan & Culver, 1895 was also recorded in the province but was later identified as M. brevirostris (Ribeiro, 1915) (Menezes et al., 2015). The presence of M. incilis Hancock, 1,830 in this region remains uncertain: a review of mullet species of South America indicated that this species does not reach the Tropical Southwestern Atlantic (Menezes et al., 2015), while some authors continue to record the species in the area (e.g., Barletta & Dantas, 2016; Freire & Araújo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to Braga et al (2001) and Silva Jr. et al (2015), sciaenids suffer a strong impact of shrimp fisheries . Considering the total biomass landed in Sergipe in 1950-2010, the Sciaenidae family also composed most of the total catch of fishes, followed by Lujanidae, Ariidae, and Centropomidae (Freire & Araújo 2016). Sciaenidae was also the family mostly represented in the bycatch of shrimp fisheries in other regions in Brazil, namely: North (Maia et al 2016, Sedrez et al 2013, Northeast, particularly in Bahia and Sergipe (Alcântara & Siqueira 2018, Santos et al 2008, Southeast (Coelho et al 1986), and South (Branco & Verani 2006, Freitas et al 2011, Schwarz Jr et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nomenclatural issues in catch statistics have been known for a long time (Freire and Pauly, 2005), but this has to be continuously monitored to allow for checking possible changes in the abundance of different shrimp species. The reconstruction process for catches off Sergipe performed by Freire and Araújo (2016), e.g., erroneously considered 'camarão-branco' (name used for the largest shrimps landed) as P. schmitti, as this was the only information available at that time. Nevertheless, these largest shrimps are mainly represented by P. subtilis in Sergipe.…”
Section: Discussionmentioning
confidence: 99%